2011
DOI: 10.2478/v10007-011-0004-8
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in cisplatin genotoxicity (micronucleus formation) in non target cells of mice by protransfersome gel formulation used for management of cutaneous squamous cell carcinoma

Abstract: Transdermal delivery of drugs offers many advantages compared to traditional drug delivery systems, including oral and injectable preparations. Due to their amphiphilic nature, lipid vesicles may serve as non-toxic penetration enhancers for drugs (1, 2). However, this approach is not very successful because of poor skin permeability, breaking of vesicles, drug leakage, aggregation and fusion of vesicles. To overcome problems of poor skin permeability, a novel vesicular system, transfersomes (ultradeformable li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…cDDP was used as the damage-inducing agent in this study due its genotoxic and nephrotoxic effects, and the kidney was evaluated as a target organ. The genotoxic mechanisms of cDDP involve chromosomal damage, as demonstrated by the induction of micronuclei ( Gupta et al ., 2011 ); the formation of cDDP-DNA crosslinks, as shown by the decrease in the percentage of DNA in the tail ( Stang and Witte, 2009 ), and the regulation of Tp53 mRNA and p53 protein levels ( Yuan et al ., 2011 ). The in vivo mechanisms of cDDP nephrotoxicity are mainly related to the induction of oxidative stress: cDDP increases free radical production ( Ognjanovic et al ., 2012 ) and decreases antioxidant enzyme activity ( Badary et al ., 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…cDDP was used as the damage-inducing agent in this study due its genotoxic and nephrotoxic effects, and the kidney was evaluated as a target organ. The genotoxic mechanisms of cDDP involve chromosomal damage, as demonstrated by the induction of micronuclei ( Gupta et al ., 2011 ); the formation of cDDP-DNA crosslinks, as shown by the decrease in the percentage of DNA in the tail ( Stang and Witte, 2009 ), and the regulation of Tp53 mRNA and p53 protein levels ( Yuan et al ., 2011 ). The in vivo mechanisms of cDDP nephrotoxicity are mainly related to the induction of oxidative stress: cDDP increases free radical production ( Ognjanovic et al ., 2012 ) and decreases antioxidant enzyme activity ( Badary et al ., 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…After that, sections were stained with hematoxylin and eosin stain (H&E stain) and examined under a light microscope at ×40. [32,33] Histopathological examination of mice skin from control (Group I), carcinogen control (Group II), methotrexate geltreated (Group III), and methotrexate loaded emulsomal geltreated (Group IV) groups was performed after the 3 rd and 6 th weeks. It was found that the skin of the control group [Figure 6(1)] has thin epidermis and normal skin layers.…”
Section: Histopathological Studymentioning
confidence: 99%
“…Localization of drugs improve long-term effectiveness [1]. This medicine is encapsulated in a vesicular medication supply to enhance the transdermal supply of liposomes, ethosomes, and transferosomes [17], but this medicinal substance may become unstable because of accumulation, hydrolysis, fusion and sedimentation during storage [18]. The delivery mechanisms of proniosomes solved vesicular system stability problems.…”
Section: Introductionmentioning
confidence: 99%